(untitled) (Journal of Universal Science Research, 2023)
This article explores the characteristics of youth slang that is commonly used on various types of social media platforms. Through a comprehensive literature review and analysis of online data, the article identifies the unique features of youth slang, including its use of abbreviations, acronyms, and emoticons, as well as its incorporation of elements of popular culture and technology. The article also examines the role of social media in the evolution of youth slang and its impact on communication among young people. Overall, the article provides valuable insights into the linguistic practices of young people on social media and highlights the importance of understanding and studying youth slang in the context of digital communication.